FORCE MAJEURE DALAM TIDAK DIPENUHINYA PRESTASI PADA PERJANJIAN JUAL BELI OKSIGEN DI MASA COVID-19 - Muhammad Aby Rafdi Al Juhdi (Magister Kenotariatan Program Pascasarjana Universitas Islam Malang, 2022)
The Covid-19 pandemic is a non-natural disaster that accidentally happened also creates a legal relationship of fulfilment for the binding agreement between the two parties. That makes the demand for oxygen increasing. This research aimed to see and analyze the non-fulfillment of achievements in an oxygen sale and purchase agreement during the Pandemic period which is included in Force Majeure as well as consequences the law in application of circumstances coerced into agreement during the pandemic. The need for oxygen during the pandemic is basic or primary and unable replaced by other goods. Various policies issued by distributors, oxygen suppliers and the government aimed to overcome oxygen scarcity for meeting people's needs, even though still not maximized yet. This research method is Normative Juridical with a review of statute, literature and supported by interviews with oxygen distributors. The object of research is the purchase contract that occurred during the Covid-19 period. This study shows that according to Presidential Decree 12/2021, the relative Force Majeure can be used as an excuse for not fulfilling achievements in the oxygen purchase agreement during the Covid19 pandemic. The legal consequences of the relative Force Majeure make producers unable to be sued for compensation from defaults because it occurs beyond human control.